BRAND EQUITY ANALYSIS OF UHT MILK PRODUCT TETRA PACK 200 ML IN YOGYA DEPARTEMENT STORE CIMANGGU BOGOR CITY - Layli Yulia Permatasari; Achmad Firman; Anita Fitriani (Fakultas Peternakan, Universitas Padjadjaran, 2022)
Cimanggu Bogor City” was carried out in August 2021, in Convenience Yogya Cimanggu, Kedung Badak Village, Tanah Sareal District, Bogor City, West Java. Purpose of the research was to know the consumer characteristics of the purchase UHT milk tetra pack 200 ml products and analyzing elements of brand equity of the purchase UHT milk tetra pack 200 ml products. The research method was a survey of 91 respondents using a questionnaire as a tool. The data obtained were analyzed using desciptive statistics analysis, Cochran test, brand switching pattern matrix, and estimated market share. According to this study, characteristic of the consumers are housewives, aged between 19-65 years old, with a monthly income of Rp. 1.000.000 - > Rp.5.000.000, a monthly expenditure of Rp. 100.000 - > Rp.3.000.000, a consumption frequency of UHT milk products per month was 1-15 times and based on calculated brand equity parameters, the results has shown that Ultramilk brand was the strongest brand equity value than competitor brand because it has superior value in dimension brand awareness, brand association, perceived quality, brand loyalty, estimated market share and more users.